Hubungan Tingkat Pengetahuan Tentang Diet Diabetes Mellitus Dengan Kepatuhan Kontrol Gula Darah pada Pasien Diabetes Mellitus Tipe II Di Wilayah Kerja Puskesmas Baki Sukoharjo - Astutik, Desiana Dwi; , Fahrun Nur, S.Kep.,Ns., M.Kes; , Arief W. Jadmiko, S.Kep., Ns., M.Kep (2016)
Diabetes mellitus is a group of metabolic diseases with hyperglycemia characteristic occurs due to insulin secretion abnormality, insulin performance or both of them. Trouble something often occurs in diabetics is how to keep blood glucose levels under control. The main pillar of diabetes treatment is the importance of education for client and family, sports, types of medicines used by client and dietary regulation.Achievement in diabetes mellitus treatment depends on diabetes mellitus patient is about adequate knowledge in order to change the attitude in conducting treatment with sugar - low diet and prevents complication so that they can live more prosperous, healthy and having quality. This research aims to determine relationship level of knowledge about diabetes mellitus diet with blood sugar control compliance in the second type patient of diabetes mellitus in Puskesmas Baki Sukoharjo. This research uses correlation descriptive by using cross-sectional design. The population of the second type patients of diabetes mellitus is 155 peoples. It was taken as sample loads of 61 peoples by using proportional random sampling technique. Independent variable in this research is level of knowledge about diabetes mellitus diet. Besides, dependent variable is compliance of blood sugar control. This research applies questioner as instrumental research. In this research, analysis Chi-square (X2) as technique of analyzing the data. There search finding shows them ostrespondents have a level of knowledge about diabetes mellitus diet is quite (44.3%), the majority of respondents classified discipline to control blood sugar as many as 52.5%. Furthermore, there is relationship of significant level of knowledge about diabetes mellitus diet and blood sugar control compliance in the second type patient of diabetes mellitus in Puskesmas Baki, Sukoharjo. It is advisable for diabetes mellitus patients to keep their health by keeping the disease condition. It means that discipline to control blood sugar, motivating to seek the information about diabetes mellitus and following some programs hospital held.